COMPARISON OF LANGUAGE ACQUISITION IN EARLY CHILDHOOD IN URBAN AND RURAL ENVIRONMENTS - Sebayang, Santa Nananda; Damanik, Bernieke Anggita Ristia (Cahaya Ilmu Bangsa Institute, 2025)
This study compares language acquisition in early childhood between urban and rural environments, focusing on the influence of environmental factors on language development. The study identifies that children in urban settings tend to have richer vocabulary, more complex sentence structures, and more frequent verbal social interactions compared to children in rural settings. Through data analysis from 100 children aged 3 to 6 years, it was found that access to media, diverse social interactions, and better educational resources in urban areas contribute to faster and more complex language development. These findings provide important insights to support educational practices and policies in children's language development.